SOLIDARNOŚĆ ZWIĄZKOWA. O ZAANGAśOWANIU NIEMIECKICH ZWIĄZKÓW ZAWODOWYCH NA RZECZ NSZZ „SOLIDARNOŚĆ” - Świder, Małgorzata (In Gremium. Studies in History, Culture and Politics, 2012)
THE SUPPORT OF GERMAN TRADE UNIONS FOR NSZZ SOLIDARNOŚĆ The events that took place in Poland were accompanied by the interest of foreign trade unions, including the Confederation of German Trade Unions (DGB), from the very first days of the unrest. The first official statement supporting Solidarność was published on 25 August 1980. The actions by DGB were based on the policy of “quiet help” for Polish opposition outlined by the German government and SPD. DGB contacted the local structures, provided help in the form of copy machines, paper, video tapes for recordings and other. There were also talks about providing organisational help. This process was disrupted when martial law was brought to life in Poland. This was the beginning of a new stage of support for Polish trade unions consisting in collecting food, medicines, hygiene supplies and funds. DGB also provided help for members of Solidarność staying in Germany at that time. Also in years 1988-1989 when perspectives of changes appeared and round-table talks took place in Poland, Solidarność was provided with material and organisational help.